Crop manuring on the Beauce plateau (France) during the second iron age. (June 2022) - Ben Makhad, Sammy; Pradat, Bénédicte; Aguilera, Mònica; Malrain, François; Fiorillo, Denis; Balasse, Marie; Matterne, Véronique
Highlights: δ 15 N values of cereal increase from 4 th to 2 nd century BCE, indicating a continuous use of manure. The variation in δ 15 N values of different grain groups within each period indicates diversity of manuring rates in the fields. Interspecific variations indicate that barley and emmer were more fertilised than free-threshing wheats. The same fertilisation strategies seem to have been applied between the three neighbouring farms. Abstract: The studied area on the Beauce plateau (France) was densely inhabited during the Iron Age and several archaeological excavations have enriched our knowledge of agrarian systems during this period. This study investigates fertilisation management between 400 and 80 BCE focusing on numerous crop storage remains from three neighbouring farms. We sampled 18 cereal groups with 50 grains to conduct stable carbon and nitrogen isotope analyses commonly used for reconstructing past agricultural practices, in particular δ 15 N as a proxy for manuring. The δ 15 N values range between 1.3‰ and 7.6‰, with an increase over time from 3.2‰ to 5.6‰ (mean by occupation phase), reflecting a continuous use of manure, consistent with the dynamism of agricultural activities during the Second Iron Age. All three farms seem to have applied the same manuring strategies. Barley and emmer may have been manured more often than free-threshing wheats, even when free-threshing wheats are the dominant crop. This contrasts with the neighbouring Ile-de-France region and indicates diversity in agropastoral systems between regions. The analysis of several grain groups from the same silo shows diversified δ 15 N values between crops, reflecting various manuring rates: some fields were fertilised while others were less so. This is consistent with the description of a large-scale farming system, with a large cultivated area and a mosaic landscape.